2019
DOI: 10.1111/tri.13412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tools for annual capture of adherence to immunosuppressive medications after renal transplantation - a single-centre open prospective trial

Abstract: Summary Annual assessment of adherence would strengthen long‐term outcome assessments from registry data. The objective of this study was to evaluate tools suitable for annual routine capture of adherence data in renal transplant recipients. A single‐centre open prospective trial included 295 renal transplant recipients on tacrolimus. Two‐thirds of the patients were included 4 weeks post‐transplant, randomized 1:1 to intensive or single‐point adherence assessment in the early phase and 1‐year post‐transplant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 50 publications
4
35
0
1
Order By: Relevance
“…Gathering information and acquiring knowledge is only a small part of managing chronic disease. The results of the Norwegian non-adherence study, mentioned above, also support these findings: although kidney transplant recipients followed a comprehensive patient education program over 8 weeks, non-adherence increased from 9% to 32% in 1 year (59). This underscores our need to have a more complex understanding of patients' behaviors and needs related to health.…”
Section: Post-transplant Follow-up and Patient Educationmentioning
confidence: 71%
See 1 more Smart Citation
“…Gathering information and acquiring knowledge is only a small part of managing chronic disease. The results of the Norwegian non-adherence study, mentioned above, also support these findings: although kidney transplant recipients followed a comprehensive patient education program over 8 weeks, non-adherence increased from 9% to 32% in 1 year (59). This underscores our need to have a more complex understanding of patients' behaviors and needs related to health.…”
Section: Post-transplant Follow-up and Patient Educationmentioning
confidence: 71%
“…Non-adherence has been found to be the third leading cause of kidney graft losses (58), and reducing non-adherence to a minimum is therefore one of the major ambitions in kidney transplant care. A recent Norwegian study revealed that 9% of kidney transplant recipients were non-adherent to medications eight weeks post-transplantation, and that the prevalence increased to at least 32% within the first year, depending on the type of tool that was used (59). Studies investigating adherence to lifestyle recommendations and graft monitoring indicate that patients are less adherent in these areas compared to medication adherence (60,61).…”
Section: Mycofenolatmofetil: Cellcept® and Myfortic®mentioning
confidence: 99%
“…Retrospective studies utilizing physician records, patient report, or clinic nonattendance to define MNA have not consistently supported a relationship between MNA and IPV 15,28,50,53 . Conflicting results have also been observed among prospective studies assessing MNA using electronic monitoring or rigorous multimodal approaches 65,73,80–82 . Although some discordance may be related to data quality pertaining to the method(s) of defining MNA or small patient population, clinicians must evaluate IPV in a patient‐specific context, including all other possible sources of IPV.…”
Section: Discussionmentioning
confidence: 99%
“…In KTx recipients, a degree of nonadherence towards immunosuppressive medication is reported to be in the range of 30%-35% and similar findings are likely for antihypertensive medication. 25 Several factors can contribute to nonadherence; hypertension is asymptomatic and medication has side effects, low health literacy, polypharmacy, forgetfulness, and poor physician-patient relationship (including the failure to consider nonadherence). 26 Low adherence was, however, only reported for 4% in the Surv resp group, which we believe reflects underreporting by the treating physicians.…”
Section: Discussionmentioning
confidence: 99%